1994
DOI: 10.3109/00048679409075880
|View full text |Cite
|
Sign up to set email alerts
|

Mental Representations of Attachment among Prospective Australian Fathers

Abstract: Research into security or otherwise of infant attachment and its correlates is well established. Research into adult internal representations of attachment is still in its infancy. This emergent area of investigation is facilitated by a new measurement instrument, the Adult Attachment Interview (AAI). This paper presents the first Australian report of the distribution of adult attachment classifications in a group of 62 men, prior to the transition to parenthood. Using the AAI, 35.4% of these men were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…The coping capacity of men with issues of emotional expression has long been taken for granted. Still, a father's sense of competence and personal attachment security to their child may be more vulnerable and vital to the mental health of fathers than has been imagined (Madsen & Juhl, 2007;Radojevic, 1994). An appropriate outlet for emotional expression, one that takes into consideration cultural factors, is a pivotal factor to consider when thinking about protective factors for fathers.…”
mentioning
confidence: 99%
“…The coping capacity of men with issues of emotional expression has long been taken for granted. Still, a father's sense of competence and personal attachment security to their child may be more vulnerable and vital to the mental health of fathers than has been imagined (Madsen & Juhl, 2007;Radojevic, 1994). An appropriate outlet for emotional expression, one that takes into consideration cultural factors, is a pivotal factor to consider when thinking about protective factors for fathers.…”
mentioning
confidence: 99%
“…Nadalje, ustanovljeno je da postoji transgeneracijski prenos sigurnog obrasca, odnosno nesigurnih obrazaca afektivnog vezivanja (vidi npr. Benoit & Parker, 1994;Fonagy et al, 1991;Radojevic, 1994;van IJzendoorn, 1995) i zato nije neobično posledično interesovanje istraživača za one aspekte roditeljstva koji su najodgovorniji za optimalan socio-emocionalni razvoj deteta, koji se, na planu ponašanja, ogleda u sigurnom obrascu vezanosti, a na nivou reprezentacionog sveta, u pozitivnim radnim modelima selfa i značajnih drugih osoba (za pregled vidi npr. Belsky & Pasco Fearon, 2008;Slade et al, 2005).…”
Section: Uvodunclassified
“…From a clinical point of view, it is compelling to note that international studies investigating adult attachment representations in non-clinical populations have demonstrated that insecure attachments are high for both men and women (van IJzendoorn & Bakermans-Kranenburg, 1994), ranging from 39% to 74% (Radojevic, 1994), although the secure pattern is modal in the vast majority of countries. Clinical populations show a strong over-representation of insecure attachment representations.…”
Section: Family Therapy Implications Elaborated I Family Therapy Maymentioning
confidence: 99%